Peran Pengasuh dalam Menerapkan Fungsi Keluarga Pada Anak Asuh di Lembaga SOS Children's Villages Medan - Rosdiana, Rosdiana; saragih, Cristina asvera (Universitas Muhammadiyah Sumatera Utara, 2024)
This study aims to analyze the role of caregivers in carrying out family functions at the SOS Children's Villages Medan Institution. This study uses a qualitative descriptive method. The subjects in this study were 7 people consisting of 1 manager of the SOS Children's Villages Medan Institution, and 6 caregivers. Data collection used interview, observation and documentation techniques. Data analysis techniques used data reduction, data presentation and drawing conclusions. Data validity used source triangulation and method triangulation. The results of the study showed that the application of family functions carried out by caregivers to foster children was based on the following functions: (1) religious function, (2) socio-cultural function, (3) function of love, (4) protection function, (5) reproductive function, (6) socialization and education function, (7) economic function, and (8) environmental development function. The role of caregivers in implementing family functions includes the role of parents, teacher, role models, educators, motivators, supervisors, advisors and managers.Keywords: Caregivers, Foster Children, Family Function, SOS Children’s Villages